Dialektika Ilmu dan Moral: Fondasi Filsafat Ilmu bagi Pendidikan Integratif - Rofi', Miftahur (Jurnal Pendidikan Madrasah, 2025)
This article discusses the urgency of integrating knowledge and morality as the foundation of holistic education capable of addressing global challenges. The philosophy of science is positioned as an epistemological framework to bridge the dichotomy between objective-oriented science and normative morality. Conceptual and thematic analysis is used to identify the ontological, epistemological, and practical dimensions of education that affirm the interconnectedness of knowledge and values. The study's findings indicate that the integration of knowledge and morality is not merely a philosophical discourse, but a practical necessity that can enhance academic quality, ethical awareness, and the spirituality of learners. However, the implementation of integration faces epistemological, methodological, and institutional obstacles that require an interdisciplinary approach, curriculum reform, and consistent institutional commitment. This finding emphasizes the importance of education that not only produces intellectually smart generations but also wise, empathetic, and socially responsible individuals. Thus, the philosophy of science contributes to strengthening an education paradigm based on integration, which is relevant to shaping perfect human beings amidst the currents of globalization. This article suggests that the integration of knowledge and morals should be made the foundation of the curriculum and national education policy, so that education can function as a dialectical space between reason, ethics, and spirituality. This reflection underscores that the sustainability of education in the 21st century can only be achieved when knowledge and morals are understood as two complementary and supportive dimensions.